Islamic Symbolism in Pro-Russian Arabic-Language Discourse on X: A Multimodal Critical Discourse Analysis - Pryimak, Oleksii (Український політико-правовий дискурс, 2026)
Purpose. The purpose of the article is to examine the discursive and multimodal articulation of Islamic symbolism in pro-Russian Arabic-language discourse on X. The article focuses on the ways in which religious references, visual markers, and evaluative captions participate in the representation of Russia and its political leadership. Methods. The study applies multimodal critical discourse analysis as the main methodological framework. This approach makes it possible to examine the interaction between textual messages, visual materials, religious markers, symbolic elements, and platform-specific forms of communication. The empirical material consists of selected publications by eight Arabic-language accounts on X that systematically disseminate pro-Russian and anti-Western narratives. The analysis focuses on the visual presentation of Islamic markers, their textual framing, their repetition across publications, and their connection with representations of Russia, Russian society, Russian political leadership, and the West. Results. The analysis shows that Islamic references and visual religious markers recur in the representation of Russia within the selected corpus. Images and videos provide recognizable religious signs, while captions assign them political and evaluative meanings. A classroom scene with a hijab-wearing teacher frames Russian education as compatible with traditional morality; a mosque for Muslim soldiers connects Islamic practice with the Russian military space; and images of mosques and Muslim women present Islam as part of Russia’s social and cultural environment. In some publications, Islamic symbolism is articulated through contrast with the West, which is associated with restriction, hypocrisy, or moral decline. This symbolic association is also personalized through Vladimir Putin: references to his alleged use of Qur’anic verses, visits to mosques, and respect for Islamic traditions present Russian political leadership as attentive to Islam and Muslim religious practice. Conclusions. The article concludes that Islamic symbolism participates in the multimodal construction of Russia’s image by linking religious signs with political evaluation. The analyzed publications incorporate Islamic markers into representations of Russia as a state where Islam is allegedly visible, practiced, and accommodated. This construction operates through visual evidence, evaluative captions, contrastive references to the West, and Putin’s personalization of respect for Islam.